The Relationship between Resilience and Parenting Stress in Single Parents with a History of Divorce Based on Roy's Adaptation Theory in Dander District - Rina Afif Alviani; Evita Muslima Isnanda Putri; ⁠Titik Nuryanti; Srimulyani Srimulyani (CV. AFDIFAL MAJU BERKAH, 2026)
The divorce rate in Indonesia is increasing sharply, posing challenges for single parents in Dander District, Bojonegoro, related to economic burden and parenting stress. This study aims to analyze the relationship between resilience and parenting stress in divorced single parents based on Roy's Adaptation Theory. Using a quantitative, cross-sectional correlational design, data were collected from 68 single parents (population 211) through a validated Resilience Scale (36 items, Cronbach's α = 0.815) and Parenting Stress Index (34 items, r = 0.912). Simple random sampling and Pearson correlation analysis in SPSS 25.0 (α = 0.05) were applied. The results showed a dominant moderate resilience (60.3%) and moderate parenting stress (56.4%), with a weakly significant negative correlation (r = -0.325, p = 0.007). In conclusion, resilience-enhancing interventions based on Roy's model are effective in reducing parenting stress, preventing negative impacts on children in rural areas.